Face Recognition Door Security System and Contactless Bell - Irnayanti, Rini; Elfizon, Elfizon (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Every human being wants to have a comfortable and safe home from various criminal acts, especially theft of valuables and crimes of assault or threats of violence. Therefore, home security is important for homeowners. In this case, a tool is made that aims to make a door security system using facial recognition biometrics and combining it with a contactless bell. Face recognition uses OpenCV based on an open source library to recognize faces in realtime using the Python programming language. This tool works by using a webcam that will be controlled by a raspberry pi 4 and arduino uno to match facial features to be detected and recognized. Arduino uno will be connected to the relay module to control the bell and selenoid doorlock to open automatically. After testing and analyzing the smart doorlock and contactless bell security system, it can be decided that this security system can work well in accordance with the design of the working principle and the results achieved according to the function and work of the tool.